Mercury (Hg)-Resistant Bacteria in Hg-Polluted Gold Mine Sites of Bandung, West Java Province, Indonesia - SITI KHODIJAH CHAERUN; SAKINAH HASNI; EDY SANWANI; MAELITA RAMDANI MOEIS (Indonesian Society for microbiology, 2012)
In the present study, ten mercury-resistant heterotrophic bacterial strains were isolated from mercurycontaminated gold mine sites in Bandung, West Java Province, Indonesia. The bacteria (designated strains SKCSH1- SKCSH10) were capable of growing well at 200 ppm of HgCl except for strain SKCSH8, which was able to grow at 550 ppm HgCl . The bacteria were mesophylic and grew optimally at 1% NaCl at neutral pH with the optimal growth temperature of 25-37 ºC. Phenotypic characterization and phylogenetic analysis based on the 16S rRNA gene sequence indicated that the isolates were closely related to the family Xanthomonadaceae, Aeromonadaceae, and Pseudomonadaceae and they were identified as Pseudomonas spp., Stenotrophomonas sp., and Aeromonas sp. Eight bacterial strains were shown to belong to the Pseudomonas branch, one strain to the Stenotrophomonas branch and one strain to the Aeromonas branch of the ã-Proteobacteria. Phylogeny based on their 16S rRNA gene sequences indicated that four of the isolates (SKCSH1, SKCSH4, SKCSH7, SKCSH9) could be classified as representatives of four novel species in the genus Pseudomonas that were allocated to P. moraviensis (96.96% similarity) and P. plecogossicida (94.53, 96.61, and 96.73% similarity). Four other isolates could be allocated to P. plecogossicida (97.57 and 98.66% similarity) and P. hibiscicola (99.97% similarity), one isolate to Stenotrophomonas africana (99.69% similarity), and one other isolate to Aeromonas hydrophila subsp. ranae (99.43% similarity). The findings of this study provide the first information of the phylogenetically-diverse Hg-resistant bacteria in the Hg-polluted sites of Indonesia that may be highly useful for developing in situ bioremediation or detoxification of Hg-contaminated sites in Indonesia.